Profitability Ratio And Stock Price Analysis Of Indonesian Food And Beverage Companies - Setiyo Hadi Santoso; I Gde Fajar Kurniawan; Putria Dewi Masruroh (GOVERNORS, 2025)
The food and beverage sector is a key pillar of the manufacturing industry, widely recognized for its resilience to economic fluctuations. This study aims to provide empirical evidence on the effect of profitability ratios on stock prices of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2017–2019 period. The main focus of this research is to evaluate the extent to which internal efficiency indicators serve as key determinants in market valuation. This study employs a quantitative approach using secondary data obtained from companies’ annual reports. The sample was selected through purposive sampling, resulting in a group of firms that consistently reported their financial performance over the three-year observation period. Data analysis was conducted using multiple linear regression to examine the partial and simultaneous effects of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on stock price movements. The findings reveal the dynamics of the relationship between profitability and market response. From the perspective of signaling theory, this study demonstrates whether increases in net profit and asset efficiency provide sufficiently strong positive signals to drive stock price appreciation in the secondary market. These results contribute to investors in formulating fundamental-based portfolio strategies and to corporate management in determining financial policy priorities aimed at optimizing shareholder value.